Analysis of Behavioral Factors For Dumping Waste at Sea on The Coastal Region - Karmila Patandean; Fikki Prasetya; Akifah (Universitas Mandala Waluya, 2021)
The problem of marine debris is inseparable from the culture of the people who are not aware not to throw garbage in the sea and the lack of communication between stakeholders. Problems with the implementation of waste management also occur in the city of Kendari, the increase in population result in the accumulation of waste person as much 0.6 kg/day or 247.96 tons/day. The purpose of the study was to determine the factors related to the behavior of people throwing garbage at sea in the coastal area of ​​Bungkutoko Village. The research method is quantitative research with cross sectional design with a sample of 231 respondents by purposive sampling using the Spearman Rank Correlation test. The results of this study indicate that there is no relationship between public knowledge and the act of throwing garbage at sea (p-value=0.545>0.05), there is no relationship between community attitudes and the act of throwing garbage at sea (p-value=0.225>0.05), there is no relationship between available facilities and the act of throwing garbage at sea (p-value=0.196>0.05), there is no relationship between local government supervision and the act of throwing garbage at sea (p-value=0.505>0.05). The conclusion in this study is that there is no relationship between community knowledge, community attitudes, available facilities or facilities, and local government supervision with the act of throwing garbage at sea. For further researchers, it is hoped that this research can be used as a reference to complete this research.